Kilka uwag o "Księdzu Piotrze" Kazimierza Przerwy-Tetmajera - Grzelak, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article analyzes short story of Tetmajer, one of the most known Polish poet at the turn of the XIX and XX century. The author of this article presents circumstances of writing Father Peter and prototypes of title hero. Tries to prove also, that work has been written influenced by fascination romantic literature.